The boundary conditions used for modeling tidal picture in the Gulf of Tonkin - Quynh, Do Ngoc; Ninh, Pham Van; Viet Lien, Nguyen Thi (Vietnam Journal of Mechanics, 1994)
The two dimensional Saint-Venant equation system is used for tidal calculation in the Gulf of Tonkin with the impermeability given at coastal line and a variation of sea level given at liquid boundaries. It is clear that data at liquid boundaries usually are very rare, while at the coast of the gulf there is a lot of data of tidal harmonic constituents. In the paper the problem how to use these constituents at coast line in modelling for raising up accuracy of the solution is considered.